2010
DOI: 10.1007/s13105-010-0054-2
|View full text |Cite
|
Sign up to set email alerts
|

Decreased glutamine synthetase, increased citrulline–nitric oxide cycle activities, and oxidative stress in different regions of brain in epilepsy rat model

Abstract: To understand their role in epilepsy, the nitric oxide synthetase (NOS), argininosuccinate synthetase (AS), argininosuccinate lyase (AL), glutamine synthetase (GS), and arginase activities, along with the concentration of nitrate/nitrite (NOx), thiobarbituric acid reactive substances (TBARS), and total antioxidant status (TAS), were estimated in different regions of brain in rats subjected to experimental epilepsy induced by subcutaneous administration of kainic acid (KA). The short-term (acute) group animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 45 publications
3
27
0
1
Order By: Relevance
“…Epileptic form activity was shown to cause excessive production of ROS/RNS, a factor believed to be involved in the mechanisms leading to neurodegeneration and cell death (Itoh and Watanabe, 2009). The increased production of NO and increased oxidative stress in kainic acid mediated excitotoxicity and epilepsy has been reported earlier (Swamy et al, 2009(Swamy et al, , 2011a.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Epileptic form activity was shown to cause excessive production of ROS/RNS, a factor believed to be involved in the mechanisms leading to neurodegeneration and cell death (Itoh and Watanabe, 2009). The increased production of NO and increased oxidative stress in kainic acid mediated excitotoxicity and epilepsy has been reported earlier (Swamy et al, 2009(Swamy et al, , 2011a.…”
Section: Discussionsupporting
confidence: 53%
“…It was earlier reported that GS becomes nitrated and inhibited during PTZ induced seizure model at repeated PTZ seizure induction, but there was no decrease in GS protein level (Bidmon et al, 2008). Our earlier studies demonstrated that increased production of NO, increased activity of NOS, decreased activity of GS and increased oxidative stress in KA mediated excitotoxicity (Swamy et al, 2009(Swamy et al, , 2011a. Therefore the present study was conducted to assess the neuroprotective effects of the bee product propolis , by estimating the glutamine synthetase activity, nitric oxide (NO), thiobarbituric acid reactive substances (TBARS) concentration and total antioxidant status (TAS) in cerebral cortex (CC), cerebellum (CB) and brain stem (BS) of rats supplemented with propolis and subjected to KA mediated excitotoxicity.…”
Section: Introductionmentioning
confidence: 87%
“…Its deficiency may couple OS to neuronal death and degeneration, thus providing the basis for novel treatment. The concentration of TBARS was increased and total AO status was decreased in epilepsy, supporting a role for OS [19]. Treatments designed to prevent lipid peroxidation may be more effective for epilepsy prophylaxis than administration of antiepileptic drugs that mask convulsive seizures while brain injury continues [20].…”
Section: Epilepsymentioning
confidence: 92%
“…Unexpectedly, it is possible to explain the increase of activity of iNOS also and decline of activity of arginase metabolism of arginine, namely for limitation of ureapoiesis, which, due to formation of ureidosuckcynate [7] can inhibit such necessary for work iNOS resynthesis of arginine from a citrulline in the citrulline loop [13].…”
Section: Resultsmentioning
confidence: 99%
“…By reliable reason of growth of iNOS activity(almost exceptionally due to induction of this enzyme) in the process of contention period for sportsmen and for sportswomen, there can be a simultaneous increase of both pools of inductors (inflammatory cytokinites of TNF, Inf-gamma, Il-1 but other) and generation of activator of induction, -super anion oxide [13]. Activating of this enzyme can have negative consequences for work of heart of sportsmen, promoting the apoptosis of cardiomiocytes [11,14].…”
Section: Resultsmentioning
confidence: 99%